Physicians’ duty to recontact and update genetic advice - Stevens, Yvonne A (Per Med, 2017)
This perspective addresses whether physicians have a duty to recontact former or current patients to update clinical advice based on newly discovered genomic information. Genetic information is unique compared with other medical data in that the underlying data do not appreciably change during the patients’ lifetime, but the clinical significance of that information will continue to evolve. Based on relevant case law and guidelines, there is no general, established legal duty for physicians to affirmatively recontact former or current patients to update clinical advice based on newly discovered genetic information. However, integration of genomics into clinical practice is advancing quickly, and there may be limited, specific situations where a physician may have a duty to provide updated genetic information.